Peran Kebijakan Tarif Dalam Menyeimbangkan Neraca Perdagangan Indonesia - Amerika Serikat - Rukmana, Kevin Anandita; Lie , Gunardi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Trade balance is an important indicator to assess the economic balance of a country in international trade relations. Tariff policies, both import and export tariffs, play a significant role in influencing the dynamics of a country’s trade balance. Tariffs are used as a protection tool to safeguard domestic industries, control the flow of imported goods, and strengthen the competitiveness of domestic products in the global market. A reduction in import tariffs can increase exports and reduce trade deficits, while an increase in import tariffs has the potential to hinder exports and enlarge trade deficits. Similarly, export tariff policies can impact the ability of domestic products to compete in international markets. The interaction between import and export tariff policies also greatly determines the balance of a country’s trade balance, where disproportionate policies can trigger tariff retaliation from trading partner countries and worsen trade conditions. Therefore, a balanced and adaptive tariff policy strategy is required to support the stability of the trade balance and sustainable national economic growth.